On Resisting Global Disposability, Regimes of Death-Making and Accumulation - Rupinder Parhar (Journal of Extreme Anthropology)
The British writer Rupinder Parhar gave a talk on feminist acts of resistance at an art exhibition workshop in London in March 2024. While acknowledging the multitude of feminisms that exist today, Parhar in this transcript of the talk asks difficult questions about the relationship between the global forces of violence that should compel us to rethink our own resistance and complicity. She also discusses our interconnection with, and need to learn from, those who ‘face the knife-edge of these global regimes of death-making’ in their everyday lives, such as in Palestine. Reminding us that struggles continue with whatever tools available to those facing these regimes of disposability, she opens up a larger conversation around what we see and accept as resisting subjects and practices. Thus, the conversation ends by prompting the audience to rethink the ways in which resistance is framed and valorised, particularly in institutional spaces, urging a more dynamic and critical approach to solidarity and action.